2020
DOI: 10.1111/plb.13088
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nitrogen in storage root growth and related gene expression in sweet potato (Ipomoea batatas)

Abstract: Nitrogen (N) could affect storage root growth and development of sweet potato. To manage external N concentration fluctuations, plants have developed a wide range of strategies, such as growth changes and gene expression.• Five sweet potato cultivars were used to analyse the functions of N in regulating storage root growth. Growth responses and physiological indicators were measured to determine the physiological changes regulated by different N concentrations. Expression profiles of related genes were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…To verify the reliability of the previously selected reference genes, NnEXPA1 was chosen for expression analysis. NnEXPA1, a member of the EXPA (α-expansin) subfamily, is associated with EXPA proteins that play a crucial role in cell wall loosening and cell expansion, contributing to various plant developmental processes such as internode elongation, root growth 29 , seed development 30 , endosperm expansion 31 , and nodule formation 32 . When employed as internal controls with different reference genes tailored to specific conditions, no significant expression discrepancies were detected among the recommended candidates.…”
Section: Discussionmentioning
confidence: 99%
“…To verify the reliability of the previously selected reference genes, NnEXPA1 was chosen for expression analysis. NnEXPA1, a member of the EXPA (α-expansin) subfamily, is associated with EXPA proteins that play a crucial role in cell wall loosening and cell expansion, contributing to various plant developmental processes such as internode elongation, root growth 29 , seed development 30 , endosperm expansion 31 , and nodule formation 32 . When employed as internal controls with different reference genes tailored to specific conditions, no significant expression discrepancies were detected among the recommended candidates.…”
Section: Discussionmentioning
confidence: 99%
“…However, N utilization in cultivars with different N tolerances has rarely been reported. N also affects storage root formation and expansion at the early growth stage, and previous studies showed that moderate N deficiency or low N conditions promote root growth and differentiation, while excessive N apparently inhibits root development (Si et al, 2018; Villordon et al, 2013; Yao et al, 2020). Moreover, a previous study showed that, under the same N levels, treatment with ammonium N resulted in higher storage root yield by promoting young root growth and development and increasing the number of storage roots during the early stage of storage root formation (Si et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…The increasing demand for sweet potatoes in recent years can be attributed to their adaptability and nutritional value. Nitrogen (N) is an important nutrient element affecting sweet potato growth [ 2 ]. Previous studies have shown that a low N supply can stimulate root growth and differentiation in sweet potatoes, while high rates of N application can lead to root lignification and hinder storage root formation [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%